Մաշտոցեան Մատենադարանի հնատիպ գրքերի ձեռագիր և գրադարանային նշումները - Մանուկեան, Տաթեւիկ; Սարգսեան, Քնարիկ (Մատենադարան)
The Armenian early printed book co-existed with the manuscript for a long time. When printing a book, the publishers and authors, as a rule, produced it following the traditions of manuscript copying, which included colophons. The colophons contain detailed information about the circumstances of the preparation and promotion of the book, the publisher, typography, author, translator and time of publication. Early printed books, besides printed colophons, contain small and large handwritten ones, which provide information not only about the printing process but also about the historical background and events of that period. Moreover, one may also see unknown literary pieces. The information gives the researcher a clearer notion about the book, whether it belonged to an academic organization or an individual before finding place in Matenadaran. The authors of colophons, both in manuscripts and early printed books, were owners, buyers, commissioners, donors and restorers who, in addition to mentioning historical events or various domestic scenes, also left genealogical records about their families and kin. In addition to handwritten colophons, library notes are also important for tracing the path of early printed books. Under the general title of library notes, we have conventionally highlighted the following types: a. inventory number, b. different protocols, c. rubber stamp (library and personal). As of July 2022, there are 2,542 copies of early printed books in the library of Matenadaran, which cover about 900 titles printed from 1512 to 1800. The project of the description of handwritten colophons and library notes in early printed books of Matenadaran started more than five years ago. We have already prepared 500 descriptions. The preparation of this corpus can be partially compared with manuscript catalogues and collections of manuscript colophons. It will be useful for studying the history of printed books and clarifying various related issues. The corpus will also be an important and rich source material for the study of the history of Armenian culture in general. Армянская старопечатная книга долгое время сосуществовала с рукописной. Издатели и авторы, как правило, составляли ее, следуя традициям создания рукописей, в частности – снабжали ее колофоном. Колофоны содержат подробную информацию об обстоятельствах создания и процессе написания книги, издателе, типографии, переводчике, авторе и времени. В старопечатных книгах, кроме печатных колофонов, встречаются малые и большие рукописные колофоны, которые дают информацию не только о печатном процессе, но и об исторических реалиях и событиях этого периода, иногда содержат и неизвестные образцы художественного творчества. Информация помогает исследователю составить более четкое представление о данной книге и позволяет установить, принадлежала ли она научной организации или личной библиотеке до поступления в Ереванский Матенадаран. Авторами колофонов, как в рукописях, так и в старопечатных книгах, были в основном одни и те же люди: владельцы, покупатели, заказчики, дарители и реставраторы, которые, помимо изображения исторических ситуаций и различных бытовых сцен, вели записи о своих семьях и родах. Библиотечные пометы также важны для отображения пути передвижения старопечатных книг. Общим названием «библиотечные пометы» мы обозначаем: а. инвентарный номер, б. различные протоколы, в. штамп (библиотечный и личный). В библиотеке Матенадарана хранится 2542 армянские старопечатные книги, которые охватывают около 900 наименований книг, напечатанных с 1512 по 1800 годы (данные на июль 2022 г.). Уже более пяти лет в Матенадаране имени Маштоца ведется работа по описанию рукописных колофонов и библиотечных записей старопечатных книг, в ходе которой удалось подготовить 500 описаний печатных книг. Несомненно, корпус будет полезен исследователям при изучении истории печатной книги. Наряду со сборниками рукописных колофонов он станет важным источником для изучения истории армянской культуры.
Keywords: Մատենագիտություն; Հնատիպ գիրքեր; Ձեռագրեր